Olhares sobre o delta do Parnaíba: conflitos na construção de um território turístico - Carvalho, Rita de Cassia Pereira de (2022)
The possibilities for understanding the territory and territorialities contribute to the understanding of the relationships that take place in the Parnaíba Delta Environmental Protection Area (APA), which are permeated by the concepts of territory, landscape and territoriality. The research refers to the relationships between tourism agencies and the communities of the APA Delta do Parnaíba, a federal conservation unit located in the states of Maranhão, Piauí and Ceará, covering 10 municipalities, namely: Paulino Neves, Água Doce do Maranhão, Tutoia, Araioses, Ilha Grande, Parnaíba, Luís Correia, Cajueiro da Praia, Chaval and Barroquinha. The subjectivities between the subject and the object of study make it possible to understand how relationships occur in this territory in its diversity. Thus, the general objective is to analyze the relations of territory and territoriality between communities/associations and tourism agencies in the APA Delta do Parnaíba. The determined methodology is based on the qualitative method to understand the meaning that individuals attribute to the interference caused by tourism activity. The subjects involved in the research are the communities, receptive tourism agencies and professors at the Universidade Federal do Delta do Parnaíba. Data were collected through interviews, a conversation circle and the analysis of a case study. From the description and analysis in the categories territory, community and tourism, as explained by Bardin (2011). The results show us that tourism agencies still do not have an effective reciprocal relationship with the communities, which should be stimulated with community engagement to promote new local productive arrangements aimed at tourism. Sources and narratives describe that communities remain stagnant waiting for actions that can provide improvements in the quality of life, when also directed to the exploitation of the APA's natural resources. In the meantime, they maintain traditional habits of artisanal work, fishing and crabbing, agriculture and raising animals for subsistence. The changes in the territory, however, cause conflicts and reveal levels of reality that were not visible until then, such as land ownership, wind farm buildings, resorts, urbanized accesses, public lighting, hotels and inns. A new scenario that disturbs the environment, creates reterritorialities and, therefore, conflicts. Reterritoriality faces the challenge of rethinking human, fauna and flora refuge. It is observed that an anthropy that is in process, involving environment, natural resources, transformative work, norms, apprehensions. A multicultural process, which also involves multiple interests in a power game.